Youth identities and social transformations in modern Indonesia - Robinson, Kathryn May, 1949- (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2016)
Youth Identities and Social Transformations in Modern Indonesia addresses current struggles and opportunities facing Indonesia's youth across the archipelago. Contributions to this volume delve into youth aspirations and their everyday lives - education; friendship; work; leisure; sexuality; religion - described through the lens of the young people themselves. They are well educated but employment is hard to find: alternative paths to adulthood can include early marriage or joining street protest movements. In public rhetoric youth is often associated with 'moral panics' related to sexual morality, and also to violent religious identities and street protests. The authors include leading scholars of Indonesia and its youth, reporting on ethnographic research from across the archipelago. Contributors are: Linda Rae Bennett, Patrick Guinness, Noorhaidi Hasan, C. Ugik Margiyatin, Pam Nilan, Lyn Parker, Kathryn Robinson, Patricia Spyer, Puju Semedi, Ben White, Tracy Wright Webster.